Degree of processing and nutritional value of children's food products - Araújo, CRBD (2021)
Objective: This study aimed to characterize the availability, the nutritional composition, and the processing degree of industrial foods for 0-36-month-old children according to the neighborhoods affluence. Design: A cross-sectional exploratory study. Setting: All food products available in retail stores for children aged 0 to 36 months were analyzed. Data collection took place in two neighborhoods, comparing two different sociodemographic districts (high versus low per capita income), Campanhã and Foz do Douro in Porto,Portugal. Participants: A total of 431commercially food products for children aged 0 to 36-month-old children sold in 23 retail stores were identified. Food products were classified according to their processing degree using NOVA. Results: For NOVA analysis, 244 food products were included being 82 (33.6%) minimally processed, 25 (10.2%) of processed and 137 (56.1%) were ultra-processed. No food product was classified as culinary ingredient.The products included mostly cereals, yogurts, prevailed in high-income neighborhoods, in the 0-6-month-old group. It was observed that some categories of ultra-processed food (UPF) presented higher amounts of energy, sugars, saturated fat and salt than unprocessed/minimilly processed products. Conclusions: The high availability of UPF offered for 0-36-month-old children should be considered when designing interventions to promote healthy diet in infancy. (c) The Authors 2021.